2016
DOI: 10.5958/2277-940x.2016.00092.9
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence Study on Goat Contagious Caprine Pleuropneumonia in Jabalpur, Madhya Pradesh

Abstract: The present study highlights the seroprevalence of contagious caprine pleuropneumonia (CCPP) in goats using slide agglutination test. A total of 1427 serum samples from goats belonging to Jabalpur district of Mahakaushal region of Madhya Pradesh were screened over a period of one year (i.e. April 2014 to March 2015). All the samples were screened for CCPP antibodies by slide agglutination test (SAT) using colored CCPP antigen. The overall seroprevalence of contagious caprine pleuropneumonia in goats was 10.65 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…capripneumoniae (Mccp) causes severe and contagious disease in small ruminants, with significant economic impact (OIE 2017). Slide agglutination test using coloured antigen is simple, fast, easy to interpret the results and low cost with ease of application in field conditions (Gupta et al 2016). This study revealed the CCPP prevalence rate of 31.27% (71/ 227) by SAT (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…capripneumoniae (Mccp) causes severe and contagious disease in small ruminants, with significant economic impact (OIE 2017). Slide agglutination test using coloured antigen is simple, fast, easy to interpret the results and low cost with ease of application in field conditions (Gupta et al 2016). This study revealed the CCPP prevalence rate of 31.27% (71/ 227) by SAT (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…capripneumoniae obtained from the Bacteriology and Mycology division of Indian Veterinary Research Institute (IVRI), Izatnagar, Uttar Pradesh was used for SAT. The slide agglutination test was performed as per the method described by Gupta et al (2016).…”
Section: Samplesmentioning
confidence: 99%
“…CCPP has been noted in Maharashtra by Suryawanshi et al (2015) and Ingle et al (2008), in Jabalpur by Gupta et al (2016), in Kerala by Abraham et al (2015); Ravishankar et al (2011) and Priya et al (2008), in Tripura by Ghosh et al (1989), in West Bengal by Guha et al (1985) and Ravishankar et al (2011) in Kanur Kerala, and Priya et al (2008) in Wayanad district of Kerala. The clinical cases of CCPP in pashmina goats of Changthang, Ladakh and in Bakarwal goats of Kashmir valley were also observed with no isolation report of the organism.…”
Section: Occurrencementioning
confidence: 93%
“…Barbari breed showed 34.69% prevalence followed by 21.43% in Black Bengal breed, 17.48% in Sirohi breed, 9.09% in Jamunapari breed and the lowest prevalence of 2.77% was noted in non-descript breed of goats. Gupta et al (2016) noted that overall sero-prevalence of CCPP in goats was 10.65%. Sero-prevalence of CCPP in organised goatry was higher (i.e.…”
Section: Prevalence Morbidity Mortalitymentioning
confidence: 98%
See 1 more Smart Citation